« Principe 7 » De La Pédagogie, Effet Zeeman-Effet Prérequis, Architecture Pyramidale Du Système Lmd: Mise En Œuvre D’une Pédagogie Discriminatoire Pour Un Enseignement De Qualité - Sakho, Ibrahima (European Scientific Journal, ESJ, 2018)
In this work, we demonstrate by analogy with the quantified levels of atomic systems, that the levels of education from elementary to Superior are "quantified". The transition of a learner from one level of instruction to another is analogous to an electronic transition between atomic levels. The notions of ground state, excited states and ionized state of atomic systems have their equivalents in the school and university systems. It is demonstrated in this work that the number 7 is revealed in all countable elements of an educational system. This leads to the statement of the "principle 7 " of pedagogy. Thus, there are 7 levels of instruction or teaching-learning in the elementary, 7 levels at the middle-level and 7 levels of teaching-learning at the higher level. In addition, there are 7 degrees, 7 hours of work of the learner in the school space. The application of "Principle 7 of pedagogy" to the determination of the number of classes per cycle and the number of students per classroom is discussed. Moreover, it is shown in this work, that the Pauli Exclusion Principle allows to account for the correct occupation of the tablesbenches by the learners and that and the indiscernibility principle of the particles accounts for the necessity of the wearing school clothes. By analogy with the Zeeman Effect, it is shown that all levels of teaching-learning are degenerate. The lifting of degeneration by "Prerequisite Effect" highlights the need to put into practice a discriminatory pedagogy for quality education at the elementary level as well as at the higher level. Finally, it is demonstrated by analogy with the tightening of the atomic levels with the increase of the principal quantum number, that the architecture of the LDM must have the appearance of a pyramid, the base being constituted by the level License and the summit by the PhD level. Moreover, the increase in the number of 180/120/180 credits does not follow the pyramidal architecture of the LMD and that it should mathematically decrease according to the ratio L / M = M / D = 3/2; which corresponds to the 180/120/80 pyramidal progression. If a credit corresponds to 20 hours of work in L and M, it should correspond to 45 hours of work in D.